The influence of oxygenotherapy on the hypercapnia in patients with chronic obstructive pulmonary disease - Lazić Zorica; Čekerevac Ivan; Novković Ljiljana; Ćupurdija Vojislav (Vojnosanitetski Pregled)
Background/Aim. Oxygen therapy is a necessary therapeutic method in treatment of severe chronic respiratory failure (CRF), especially in phases of acute worsening. Risks which are to be taken into consideration during this therapy are: unpredictable increase of carbon dioxide in blood, carbonarcosis, respiratory acidosis and coma. The aim of this study was to show the influence of oxygen therapy on changes of arterial blood carbon dioxide partial pressure. Methods. The study included 93 patients in 104 admittances to the hospital due to acute exacerbation of CFR. The majority of the patients (89.4%) had chronic obstructive pulmonary disease (COPD), while other causes of respiratory failure were less common. The effect of oxygenation was controlled through measurement of PaO2 and PaCO2 in arterial blood samples. To analyze the influence of oxygen therapy on levels of carbon dioxide, greatest values of change of PaO2 and PaCO2 values from these measurements, including corresponding PaO2 values from the same blood analysis were taken. Results. The obtained results show that oxygen therapy led to the increase of PaO2 but also to the increase of PaCO2. The average increase of PaO2 for the whole group of patients was 2.42 kPa, and the average increase of PaCO2 was 1.69 kPa. There was no correlation between the initial values of PaO2 and PaCO2 and changes of PaCO2 during the oxygen therapy. Also, no correlation between the produced increase in PaO2 and change in PaCO2 during this therapy was found. Conclusion. Controlled oxygen therapy in patients with severe respiratory failure greatly reduces the risk of unwanted increase of PaCO2, but does not exclude it completely. The initial values of PaO2 and PaCO2 are not reliable parameters which could predict the response to oxygen therapy.